(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In the article, there is a vivid demonstration of mechanisms aimed at enhancing the professional competence of future technological education teachers. The development of theoretical and practical forms of professional activity is based on fostering creative thinking, abilities, a penchant for creativity, interest, and the expression of distinct characteristics tied to intellectual, subject-specific, and motivational factors in professional situations.